Factor that affect knowledge sharing among employees in multinational organization - Hassan Al-Qadhi, Yaser Hassan (2013)
Knowledge is regarded as the most important resource, and it has often been described as the driving force towards the sustainable and key source of competitiveness. Knowledge management has been described as a collection of strategies and practices used in an organization to discover, create, share, transfer, and enable adoption of insights, experiences and knowledge resources embodied in individuals or embedded in organizations as processes or practices. Knowledge sharing is seen as the most important aspect of knowledge management. No doubt, many studies have shown that knowledge sharing is essential for firms’ performance. The purpose of this study is to investigate the relationship between trust, management support, mutual reciprocity, self-efficacy, altruism and knowledge sharing as well as to identify the level of knowledge sharing among multinational employees in an organization in Saudi Arabia. In order to test these relationship five hypotheses was proposed. Two hundred and forty five questionnaires were distributed to the sample population. One hundred eighty nine questionnaires were used to test the results of this study. Multiple regressions were used to analyze the data. The results of the study indicate that trust and management support have a positive influence on knowledge sharing. However, interestingly and surprisingly, the multiple regression results showed that the mutual reciprocity, self-efficacy and altruism have insignificant influences on knowledge sharing. In addition, trust is considered as the factor the contributed the most to knowledge sharing. Taking these factors into consideration will guarantee the success of knowledge management initiatives in the organization.